PERFORMANS REPRODUKTIF IKAN PATIN SIAM (PANGASIUS HYPOPTHALMUS) DALAM MERESPONS TINGKAT PENAMBAHAN TEPUNG KROTO PADA FORMULASI PAKAN BERBASIS BAHAN BAKU LOKAL - Amrih Joko Waspada (Universitas Padjadjaran, 2012)
kroto flour feed formulation based on local raw materials has been implemented in Research Center and Breeding Freshwater Aquacultur Technology Sukamandi, Subang, West Java from June to August 2011. This research used completely randomized design with four treatments: treatment with no addition of kroto flour (control), treatment with addition of kroto flour 5%, 10% and 15%. Each treatments was repeated four times. The results showed that the treatment which adding kroto flour showed reproductive performance (response of eggs fecundity per kilogram, fertilization rate, hatching rate, and larval survival rate) higher than control. No significant reproductive performance response for the addition of kroto flour rate of 5%, 10%, 15%.